2020
DOI: 10.1002/iub.2390
|View full text |Cite
|
Sign up to set email alerts
|

The apoptosis‐inducing factor family: Moonlighting proteins in the crosstalk between mitochondria and nuclei

Abstract: In Homo sapiens, the apoptosis‐inducing factor (AIF) family is represented by three different proteins, known as AIF, AMID and AIFL, that have in common the mitochondrial localisation in healthy cells, the presence of FAD‐ and NADH‐dependent domains involved in an ‐albeit yet not well understood‐ oxidoreductase function and their capability to induce programmed cell death. AIF is the best characterised family member, while the information about AMID and AIFL is much scarcer. Nonetheless, available data support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 92 publications
(156 reference statements)
0
25
1
Order By: Relevance
“…Its capacity to trigger cell death is controlled in part by its association with other proteins including HSP70 and cyclophilin A ( Candé et al 2004 ). The protein contains multiple conserved domains including two FAD domains and an NADH binding domain, and its function is controlled in part by redox-dependent conformational changes ( Herrmann and Riemer 2020 ; Novo et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its capacity to trigger cell death is controlled in part by its association with other proteins including HSP70 and cyclophilin A ( Candé et al 2004 ). The protein contains multiple conserved domains including two FAD domains and an NADH binding domain, and its function is controlled in part by redox-dependent conformational changes ( Herrmann and Riemer 2020 ; Novo et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The interstitial connective tissue of mammalian testes is composed of different ingredients,such as blood capillaries,lymphoid vessels and Leydig cells.Leydig cells in testicular sections play crucial roles in male development and the maintenance of reproductive functions [23].We have demonstrated that the swelling of mitochondria in Leydig cells was related to oxidative stress in cryptorchid yaks [24]. Novo et al [25] revealed that oxidative stress mediates mitochondrial dysfunction and programmed cell death.In the present study,the villus protrusions of Leydig cells were not obvious and with swelling mitochondria and indistinct reticulum crowding in the cytoplasm of Leydig cells in cryptorchidism.A previous study focused on the similarities between aging-associated and cancer-associated oxidative stress and mitochondrial dysfunction as their common phenotype [26].In our study,the pathological changes of cryptorchidism in camel should be closely related to the decrease in oxidative capacity of swollen mitochondria in Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting bidirectional relationship exists between the mitochondria and the nucleus [ 9 ]. Following nuclear DNA damage promoted by different inducers (e.g., ultraviolet light, DNA-damaging drugs, etc.…”
Section: Introductionmentioning
confidence: 99%